On the type series of Hylodes petropolitanus Wandolleck, 1907 (Anura, Cycloramphidae), with taxonomic considerations of Eupsophus fuliginosus Fitzinger, 1861 - Sabbag, Ariadne fares [UNESP]; Baeta, Delio; Grant, Taran; Feio, Renato n.; Haddad, Celio F. B. [UNESP] (Amer Museum Natural History, 2025)
Thoropa comprises seven recognized species, including T. bryomantis, T. lutzi, T. megatympanum, T. miliaris, T. petropolitana, T. saxatilis, and T. taophora. It was believed that the syntypes of T. petropolitana were destroyed during the Dresden bombings in World War II; however, there are two extant syntypes of T. petropolitana in the amphibian collection of the American Museum of Natural History where they were transferred from the Staatlichen Museum f & uuml;r Tierkunde Dresden in 1923. Herein we designate a lectotype for T. petropolitana and provide a taxonomic history of the species, a synonymy, a redescription, a summary of its geographic distribution, and comments about its conservation. We also review the taxonomic status of Eupsophus fuliginosus Fitzinger, 1861, and discuss its implication for the taxonomic status of T. petropolitana.